Materialidades e simbolismos do Barco-de-fogo em Estância/SE - Ramos, Luan Lacerda (2018)
The production of Barco-de-Fogo is a traditional activity that has become a defining trait of the Estância municipality, located in Sergipe. Barco-de-Fogo consists of a small boat made out of wood and cardboard creatively decorated. The Barco-de-Fogo is stuffed with pieces of bamboo filled with gunpowder then attached to a wire before being lit, creating a unique spectacle of light during its seconds-long race along the wire. Through this practice, the creators of the artifact generate a wide set of meanings and materialities that vivify the municipality’s streets during the June festivities. Our biggest purpose is to analyze the relationship between the producers of Barco-de-Fogo from the Porto D’Areia neighborhood, taking into account their practices and future projections related to this knowledge/practice, since it started on this neighborhood. The research is outlined using a qualitative research approach and case studies, executed following the premises of the phenomenology of perception method. The research proceedings include the application of semi-structured interviews, free observation, photographic recording and survey, institutional data collection, and bibliographic revision. The data and information collected by the respective proceedings will be analyzed through discourse analysis (Orlandi, 2009), in parallel with social mapping — recommended so that the researcher, considered an outsider by the individuals living in the area being studied, are able to understand the territorial outlines pointed at by the individuals involved directly or indirectly with the studied phenomena (Tim Ingold, 2005). The hope is that the research’s directives will allow us to: learn about the activities and occupations of the Barcode-Fogo producers; survey the materialities and the meanings of this production to its producers; learn their perspectives for the future and understand the level of economic, social, and cultural importance of this production across multiple scales. Until the present moment, it’s been noted that the producer’s territorial outline reveals a history that legitimizes the relations ship between producers and community, demonstrating that the Barco-de-Fogo is seen as a symbol of culture and identity by the people of the Estância municipality and the state of Sergipe. Taking that into account, the matter we mean to reveal/affirm is whether the symbolic nature of the Barco-de-Fogo represents the (re)production of the community’s life and the producers’ in times past and present.